Mobile operation and maintenance system of electric power communication access network based on IoT technology - Haiming JIANG; Danni XIA; Yuan LIU; Shiwen ZHAO; Lin FEI; Jingyu REN (Dianxin kexue)
The mobile operation and maintenance system of electric power communication access network was designed.In this developed system,the technology with intelligent identification of internet of things and data real-time transmission was introduced to the on-site operation and maintenance standardization management of the power communication network.First of all,the mobile operation and maintenance system architecture was built to realize the informatization of on-site operation and maintenance.And then,the TOPSIS algorithm was utilized to allocate the worksheet automatically,which improved the efficiency of fault processing.Besides,by real-time monitoring the site through the system,the intelligent management of the power communication access network was realized.The test results show that the operational management system is able to realize resources unified management,fault intelligent analysis,informatization support of on-site operations management,and also greatly enhance the intelligent operation and management level of power communication access network.